Increasing Loyalty Through Satisfaction at Coffee Shops in Yogyakarta - Putra Dinata, Angga (Jurnal Multidisiplin Indonesia, 2023)
The effect of brand image and servicescape on loyalty through satisfaction at Coffee Shop in Yogyakarta. This research is causality research (cause-and-effect relationship) with a quantitative approach. The population in this study were buyers who had visited Coffee Shops in Yogyakarta in the period March 2023 to August 2023 and who had visited Coffee Shop in Yogyakarta with a sample of 200 respondents. The sampling method used is nonprobability sampling with sampling techniques where the population size is unknown, the Roscoe method is used. The analysis in this study used Partial Least Square (PLS). The results of the analysis show that brand image has a positive and significant effect on satisfaction. Servicescape has a positive and significant effect on satisfaction. Brand image has a positive and significant effect on loyalty. Servicescape has a positive and insignificant effect on loyalty. Satisfaction has a positive and significant effect on loyalty. Brand image has a positive and significant effect on loyalty through satisfaction. Servicescape has a positive and significant effect on loyalty through satisfaction at a Coffee Shop in Yogyakarta.